2018
DOI: 10.18502/kss.v3i10.2911
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Women As Environmental Activist in Resolution of Environmental Conflicts for Sustainability of City

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
1
1
0
2
Order By: Relevance
“…The findings imply that the low participation of women in environmental conservation discourages environmental conservation initiatives. The findings imply that much would be achieved if women were actively involved in environmental conservation which concurs with the findings by Asteria et al (2018) showed that women who become environmental activists play a crucial role in mediating environmental conflicts and raising awareness about sustainable environmental management. The results show that 112 (30.4%) of the women agreed that there are several environmental conservation programmes in the community, 95(25.7%) disagreed, 64 (17.3%) were neutral, 59 (16%) strongly disagreed while 39 (10.6%) strongly agreed.…”
Section: Environmental Conservation Initiativessupporting
confidence: 85%
See 1 more Smart Citation
“…The findings imply that the low participation of women in environmental conservation discourages environmental conservation initiatives. The findings imply that much would be achieved if women were actively involved in environmental conservation which concurs with the findings by Asteria et al (2018) showed that women who become environmental activists play a crucial role in mediating environmental conflicts and raising awareness about sustainable environmental management. The results show that 112 (30.4%) of the women agreed that there are several environmental conservation programmes in the community, 95(25.7%) disagreed, 64 (17.3%) were neutral, 59 (16%) strongly disagreed while 39 (10.6%) strongly agreed.…”
Section: Environmental Conservation Initiativessupporting
confidence: 85%
“…Furthermore, NTFP use reinforces women's selfesteem and strengthens family and community ties. The findings of a study conducted by Asteria, Brotosusilo and Apriana (2018) showed that women who participate as environmental activists play a vital role in mediating environmental conflicts and raising awareness about environmental management for sustainability in the cities of Jakarta and Kota Tasikmalaya in Indonesia. On the other hand, a study by Mago and Gunwal (2019) established that women are key players in managing natural resources at both family and community levels and are disproportionately impacted by environmental degradation.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…Proses yang dilakukan dalam rangka membangun komitmen ini dilakukan melalui komunikasi yang menitikberatkan pada musyawarah atau kesepakatan (Rinawati, 2004). Mereka berpartisipatif dalam pembuatan keputusan dan melakukan pegawasan yang nantinya memberikan manfaat bagi keluarga, komunitas, dan lingkungan sekitar (Asteria, Brotosusilo, & Apriana, 2018). Keterlibatan perempuan dalam komunikasi partisipatiff ini murni atas panggilan hati dan kesadaran tanpa adanya iming-iming ekonomi berbeda dengan temuan penelitian (Ainiyah, 2016) yang menyatakan perempuan melakukan komunikasi dengan perempuan lainnya dengan tujuan ekonomi.…”
Section: Pembahasanunclassified
“…Sukarelawan juru pantau jentik sebagai obyek riset ini terdiri dari perempuan yang semuanya berprofesi sebagai ibu rumah tangga yang secara sukarela mereka berkomitmen untuk menjaga lingkungan dari jentik nyamuk untuk pemutusan rantai penularan DBD berupa pencegahan terhadap gigitan nyamuk Aedes aegypti dan Aedes albopicus. Sukarelawan ini mampu membuktikan kemampuan mereka untuk memfasilitasi, mediasi, komunikasi dan melakukan kordinasi (Asteria, D., Brotosusilo, A., & Apriana, I. W. A., 2018).…”
Section: Pembahasanunclassified